(untitled) (Research, Society and Development, 2022)
In the current COVID-19 pandemic, physical activity has been decreasing. In contrast, sedentary behavior largely increased due to social isolation. This scenario led to a significant worsening of population physical and mental health. With the increasing vaccination rate, many countries are coming back to normal life, but the fear of COVID-19 and crowding places can limit the physical activity practice in traditional exercise facilities, such as gyms. Given that physical activity is a nonpharmacological tool to enhance health and prevent a multitude of non-communicable diseases, it is important to achieve recommended levels of physical activity after the COVID-19 pandemic. In this opinion article, we aimed to alert about the deleterious effects of sedentary behavior associated with physical inactivity due to COVID-19 pandemic and post-pandemic scenarios. Moreover, we provide alternative strategies (exergames and high-intensity interval exercise) for individuals to maintain their activity in their homes or outdoors, avoiding traditional exercise facilities for practicing physical activity where there is potential crowding.